2016
DOI: 10.1038/icb.2016.61
|View full text |Cite
|
Sign up to set email alerts
|

Actin polymerization‐dependent activation of Cas‐L promotes immunological synapse stability

Abstract: The immunological synapse formed between a T cell and an antigen presenting cell is important for cell-cell communication during T cell mediated immune responses. Immunological synapse formation begins with stimulation of the T cell receptor (TCR). TCR microclusters are assembled and transported to the center of the immunological synapse in an actin polymerization-dependent process. However, the physical link between TCR and actin remains elusive. Here we show that lymphocyte-specific Crk-associated substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 107 publications
1
24
0
Order By: Relevance
“…This was accompanied by decreased recruitment to the IS of phosphotyrosine proteins, including phospho-ZAP70. In addition, accumulation at the IS of the mechanosensor pCASL, which is essential for the establishment of IS stability (81), and of TALIN, a known DOCK8 interactor crucial for IS stability, was reduced in Dock8 -/-Tregs. DOCK8-deficient Tregs were significantly less efficient at transendocytosis of CD86 from CHO cells, a system that relies on Treg interactions with CD86 exclusively These findings suggest that DOCK8 has a critical role in the formation of a stable IS between Tregs and DCs and in transendocytosis.…”
Section: /Dock8mentioning
confidence: 99%
“…This was accompanied by decreased recruitment to the IS of phosphotyrosine proteins, including phospho-ZAP70. In addition, accumulation at the IS of the mechanosensor pCASL, which is essential for the establishment of IS stability (81), and of TALIN, a known DOCK8 interactor crucial for IS stability, was reduced in Dock8 -/-Tregs. DOCK8-deficient Tregs were significantly less efficient at transendocytosis of CD86 from CHO cells, a system that relies on Treg interactions with CD86 exclusively These findings suggest that DOCK8 has a critical role in the formation of a stable IS between Tregs and DCs and in transendocytosis.…”
Section: /Dock8mentioning
confidence: 99%
“…Specifically, DOCK8 deficiency was correlated with low actin foci formation, and lower phosphorylation levels of the mechanosensory molecule CasL (a member of the mechanosensitive CAS family). Accordingly, a separate study showed that actin polymerization is important for CasL phosphorylation in TCR MCs, highlighting the function of CasL in bridging between mechanical forces and the T‐cell cytoskeleton . Besides actin filaments and myosin motor proteins, microtubules were also recently observed to regulate T‐cell traction forces .…”
Section: Mechanical Regulation Of Tcr and Bcr Signalingmentioning
confidence: 98%
“…Accordingly, a separate study showed that actin polymerization is important for CasL phosphorylation in TCR MCs, highlighting the function of CasL in bridging between mechanical forces and the T-cell cytoskeleton. 155 Besides actin filaments and myosin motor proteins, microtubules were also recently observed to regulate T-cell traction forces. 156 In this case, inhibiting microtubule dynamics led to an increase in T-cell traction stress, and it was found that microtubules induce this effect by regulation of myosin II phosphorylation, and inhibition of ARF.…”
Section: Mechanical Regulation Of Tcr and Bcr Signalingmentioning
confidence: 99%
“…The immunological synapse of a T cell represents one such microcosm of signaling, regulating signals at the interface with the antigen‐presenting cell to dictate T‐cell fate and to provide a conduit for T‐cell‐mediated cytotoxicity. In this issue of ICB , Santos et al 1 show how initial T‐cell receptor (TCR) signals control actomyosin contractility to mediate molecular trafficking in the immunological synapse. The back‐and‐forth between chemical and physical signals described here provides a fascinating glimpse of complex biophysical events that might well be prevalent throughout biology.…”
mentioning
confidence: 99%
“…The findings by Santos et al 1 were obtained using total internal reflection fluorescence (TIRF) microscopy on lipid bilayers. This technology is widely used, and the combination of high resolution and precise control of TCR signaling has proven very powerful.…”
mentioning
confidence: 99%